Design of Inventory Information Systems at CV Company. Web-Based Berjaya Jaya Abadi - Samsudin; Bisri, Cholil (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
This research focuses on the design and implementation of a web-based inventory management system for CV. Berjaya Jaya Abadi company. Inventory management plays a crucial role in the efficient operation of businesses, particularly in ensuring optimal stock levels, minimizing costs, and improving overall productivity. The proposed system aims to streamline inventory-related processes by providing real-time access to inventory data, facilitating inventory tracking, and automating inventory management tasks. Utilizing web-based technology offers the advantage of accessibility from anywhere with an internet connection, allowing employees to manage inventory remotely and enhancing collaboration among team members. The system will include features such as inventory tracking, stock level monitoring, order management, and reporting functionalities to provide comprehensive support for inventory management tasks. By implementing this web-based inventory system, CV. Berjaya Jaya Abadi can expect improved efficiency, accuracy, and visibility in their inventory management processes, ultimately leading to better decision-making and business performance.